A moderate microcurrent-density window enhances apparent CO2 fixation in Scenedesmus quadricauda - Ding Tan; Xin Li; Yunhui Li; Xingjia Fu; Wenyan Peng; Yun Liu (Bioresource Technology, 2027)

An undescribed tirucallane-type triterpenoid with anti-inflammatory activity from Ailanthus altissima - Zhong-Fu Wang; Xiang Guo; Li Huang; Li-Lian Zhao; Jie Li; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

Low-salt closed-loop management of secondary gallium resources: From selective recovery to high-purity upgrading - Wenhuan Guo; Jintao Fu; Weijun Zhang; Wanxian Li; Qianqian Liu; Yun Bai; Hongxiang Xu; Yijun Cao; Daoguang Teng (Journal of Environmental Management, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Collagenase-embedded self-healing hyaluronic acid/carboxymethyl chitosan hydrogel with controlled drug release: Boosting chemotherapeutic penetration and efficacy in pancreatic cancer - Jingrong Huang; Jinlin Wu; Yuao Zhang; Yongxia Cui; Ke Yuan; Zihan Zhu; Tao Li; Yun Lu; Kang Xiong; Haowen Pang; Shaozhi Fu (Chemical Engineering Journal, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Glycyrrhizic acid nanofibrils as potent ice recrystallization inhibitors: mechanism and application in ice cream - Zhanghanyu Liu; Yinling Liu; David Everett; Yun Zhai; Wenhui Qi; Yuying Fu; Teng Li (Food Research International, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Integrating stereoselective synthesis and molecular–behavioral approaches to characterize aggregation pheromone in the German cockroach - Yun Zhou; Jianan Wang; Xiaoyang Li; Jionglin Wang; Yueru Zhang; Xiaochen Fu; Yinan Qi; Jinlong Han; Feng Zhang; Qinghua Bian; Jiangchun Zhong; Chenggang Shan; et al. (Insect Biochemistry and Molecular Biology, 2026)

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Radiative cooling coatings and natural ventilation in urban street canyons: Synergies and trade-offs - Cheng-Peng Ma; Yu-Fei Tang; Shang-Xian Zhao; Gui-Xiong Yang; Fu-Yun Zhao; Yuguo Li; Rongpeng Zhang (Building and Environment, 2026)

Data driven analysis on changing patterns of reactive nitrogen deposition in East and Southeast Asia - Jiani Tan; Yan Zhang; Xuejun Liu; Yun Fat LAM; Mohd Talib Latif; Kasemsan Manomaiphiboon; Joshua S. Fu; Maggie Chel Gee Ooi; Ling Huang; Yangjun Wang; Hui Chen; Kun Zhang; et al. (Atmospheric Environment, 2026)

A seismic frequency extension and fault enhancement method based on the Fourier neural operator - Yifan Cheng; Li-Yun Fu; Jiaxuan Zhang; Shaozheng Yan (Applied Geophysics, 2026)

Microscopic Hydraulic–Mechanical Coupling Fracturing Behavior and Failure Mechanisms of Reservoir Rocks - Zhi Zhao; Zhi-Hong Li; Yun-Gang Duan; Liang-Fu Xie; Zheng Li; Guo-Feng Yu; Xiao-Ping Zhou (Rock Mechanics and Rock Engineering, 2026)

Cuproptosis: a novel mechanism and 3PM-oriented therapeutic strategy for cancer - Ding Yang; Wei-Ting Hu; Miao Li; Fang-Qing Shen; Hao-Yu Wang; Jin-Ying Ye; Fu-Lu Ren; Yun Wang (EPMA Journal, 2026)

Positive Atlantic Multidecadal Oscillation–La Niña synergy enhances recent East Asian dust activity via hydrothermal anomalies - Ruibo Zhao; Xiaoming Feng; Changjia Li; Yun Yang; Lindsay C. Stringer; Bojie Fu (Science Bulletin, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

Wave Equation Based Joint Velocity and Q Tomography with Local Traveltime Measurements - Qing-qing Li; Xin Tang; Li-yun Fu (Applied Geophysics, 2026)

Two new aromatic meroterpenoids from the fruiting bodies of Ganoderma calidophilum - Wei Liu; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Phytochemistry Letters, 2026)

Accelerated degradation of antibiotics via UV irradiation in the presence of chlorite: roles of reactive species, degradation pathways, and toxicity - Yu-qiong Gao; Xue-ting Ren; Yang-yang Liu; Ju-xiang Chen; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2026)

Synergistic and antagonistic interactions drive DOM dynamics in industrial effluents: Insights from double difference EEM analysis - Jiancheng Li; Bin Wang; Zhichao Yun; Yu Yang; Fu Xia; Xu Han; Qiyuan Liu; Yonghai Jiang; Junwen Hou (Journal of Environmental Chemical Engineering, 2026)

Artificial regulation of aerobic and anaerobic layers interface enhanced efficient nitrogen removal by weaving insulating grid and conductive carbon fiber in membrane aerated biofilm reactor - Weichao Li; Jingyu Li; Yun Wu; Meixuan Chen; Yangfan Fu; Wei Li; Shuang Liu; Jie Wang; Yingbo Chen (Bioresource Technology, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Quantitative scattering analysis of rough surface based on the boundary scattering matrix - Yang-pu Chen; Li-Yun Fu; Qing-qing Li; Hong-en Li; Qing-he Meng (Applied Geophysics, 2026)

Construction of metal-free 1D/2D hybrid through engineered structure evolution strategy for boosting photocatalytic hydrogen production - Jiahui Fu; Pingfan Zhang; Lei Wang; Wenli Zhang; Min Zhang; Yun Wang; Chunmei Li; Hongjun Dong (Journal of Water Process Engineering, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

In situ construction, characterization, and bioavailability of nano-iron oxide-whey protein isolate amyloid fibrils carriers - Huanhuan Su; Hao An; Jianzhi Yang; Khizar Hayat; Ahmad Mohammad Salamatullah; Teng Li; Yuying Fu; Yun Zhai (Food Research International, 2026)

Controllable preparation of whey protein isolate fibrils-oxidized dextran covalent complex as a delivery vehicle for enhancing iron bioavailability - Haifeng Wang; Yingxuan Xie; Huanhuan Su; Khizar Hayat; Ahmad Mohammad Salamatullah; Teng Li; Yuying Fu; Yun Zhai (Food Research International, 2026)

Fe(Ⅱ)-crosslinked whey protein fibril / iota-carrageenan complex gel for pH-responsive iron controlled release - Xuelian Yin; Qing Wang; Teng Li; Yuying Fu; Yun Zhai (Food Hydrocolloids, 2026)

Cytoskeletal control of development and environmental adaptation in plants - Yi Zhang; Jiejie Li; Yun Xiang; Pengwei Wang; Jie Le; Yanping Jing; Ting Wang; Xiangfeng Wang; Lei Zhu; Dong Qian; Guangda Wang; Peiwei Liu; et al. (Science China Life Sciences, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Hydroxypropyl methylcellulose enhances locust bean gum-mucin interactions: Implications for curcumin migration in mucus - Haifeng Wang; Jiang Mou; Teng Li; Chi-Tang Ho; Yun Zhai; Yuying Fu (Food Hydrocolloids, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Cochliomycin H, a new 12-membered resorcylic acid lactone from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Jiu-Jiu Zhou; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; You-Hua Liu; Zhao You-Xing (Natural Product Research, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Modelling temporal variations of direct-wave DAS traveltimes and amplitudes caused by CO2 injection - Wanting Hou; Olivia Collet; Li-Yun Fu; Roman Isaenkov; Roman Pevzner; Pavel Shashkin; Boris Gurevich (International Journal of Greenhouse Gas Control, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

The comprehensive fingerprints of VOCs from complex coking emissions and their temporal evolution in the atmosphere based on backward inference method - Hongyan Li; Shidan Huang; Yuanchun Ren; Yanru Zhang; Jing'’ai Bai; Hongyu Li; Guozhong Zhang; Xueying Gao; Yang Cui; Lili Guo; Jie Fan; Yongchun Liu; et al. (Atmospheric Research, 2026)

Two-Temperature Thermoporoelastic Modeling of Experimental Data for Wave Propagation in Glycerin-Saturated Tight Sandstones - Nianqi Li; Li-Yun Fu; José M. Carcione; Wubing Deng (Rock Mechanics and Rock Engineering, 2026)

The persistent threat of Niphades castanea to China’s chestnut across three major river basins - Bin Mao; Yue Fu; Ya-Bo Liu; Hui-Ling Yang; Yun-Li Xiao (New Forests, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Milk-derived peptide fibril‐iron nanoparticles prepared by a coordination-driven in-situ reduction approach with high bioavailability and sustained iron (II) protection - Huanhuan Su; Yun Zhai; David Julian McClements; Teng Li; Yuying Fu (Food Research International, 2025)

Covalent engineering of pectin-whey protein isolate conjugates enhances mucoadhesion and bioaccessibility of curcumin microparticles: Strategic impacts of crosslinking modalities - Haifeng Wang; Ting Fang; Ying Chen; Jiang Mou; Teng Li; Yuying Fu; Yun Zhai (Food Chemistry, 2025)

Enhanced degradation of pharmaceutical contaminants by medium-pressure UV irradiation in the presence of nitrate: Reactive species, toxicity and DBPs formation - Xiang-mei Zhong; Xiang Fu; Yu-qiong Gao; Yang-yang Liu; Xue-ting Ren; Ji-yue Li; Lei Li; Nai-yun Gao (Environmental Research, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Roles of Immunity and Endogenous Retroelements in the Pathogenesis of Rheumatoid Arthritis and Treatment Strategies - Mingyang Li; Yuanyuan Sun; Xueting Shan; Yuhong Tong; Yite Fu; Xiang Ma; Zhongxin Sun; Yun Xiang; Yidan Zhu; Tao Wang; Xin Wang; Jufang Zhang; et al. (Functional & Integrative Genomics, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

RNA interference targeting cytochrome P450 cyp303a1 on the performance of Henosepilachna vigintioctopunctata - Kai-Yun Fu; Miao He; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2025)

Supersaturation mechanisms and regulation strategies in nucleation-induced crystallization for high-purity fluoride recovery from photovoltaic wastewater - Zhihao Fu; Yadong Wang; Xuan Shi; Danheng Zhou; Zhilin Li; Pengkang Jin; Kunhao Li; Guohua Zhang; Ang Mei; Bingjie Sun; Yun Zhang (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

Real-time uncertainty quantification for KLT-based displacement estimation - Kang Zhou; Ming-Gang Duan; Ji-Yang Fu; Yun-Cheng He; Zi-Tong Li; Hai-Ou Shi; Jing Song (Engineering Structures, 2025)

Alkyl chain engineering in β-linked dimer acceptors: Balancing crystallinity and phase separation for high-performance organic photovoltaics - Yun Li; Jiawei Fu; Hang Jiang; Zhongwei Ge; Haisheng Ma; Yinuo Yang; Xiaobo Sun; Shouchun Yin (Chemical Engineering Journal, 2025)

Donor macrophage pyroptosis contributes to the development of aGVHD - Xueyan Sun; Qingyuan Qu; Qi Chen; Fengqi Liu; Haixia Fu; Yuxiu Chen; Menglin Li; Yun He; Xiaolu Zhu; Xiangyu Zhao; Yu Wang; Xiaojun Huang; et al. (Science China Life Sciences, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

Real-time identification and spatial distribution mapping of weeds through unmanned aerial vehicle (UAV) remote sensing - Weisong Luo; Qifan Chen; Yubo Wang; Di Fu; Zhiwen Mi; Qifan Wang; Huibin Li; Yun Shi; Baofeng Su (European Journal of Agronomy, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Characterization and source analysis of trace metal pollution in coastal shallow marine sediments, Wanning area, Hainan Island, China - Suimiao Wang; Xianqing Wang; Zhaofan Wang; Guangfei Guo; Liang Chen; Zanhui Huang; Dinghui Fu; Pingru Li; Xiuyu Yun (Frontiers in Marine Science, 2025)
Introduction Coastal shallow marine sediments serve as important sinks for trace metals and are crucial indicators of anthropogenic pollution. The Wanning area of Hainan Island has experienced rapid coastal development and intensified aquaculture, raising concerns about metal contamination. Methods In this study, 57 surface sediment samples were collected from the coastal shallow sea of the Wanning area. The concentrations of seven trace metals (As, Hg, Cu, Zn, Cd, Pb, and Cr) were determined. Pollution levels were evaluated using the Nemero multifactor pollution index, and source apportionment was conducted through the Positive Matrix Factorization (PMF) model. Results The average concentrations of As, Hg, Cu, Zn, Cd, Pb, and Cr were 11.40, 0.037, 11.36, 51.69, 0.10, 24.53, and 45.86 mg/kg, respectively, which generally comply with China’s Class I Marine Sediment Quality Standard. While the overall pollution level was low, localized hotspots of As, Cu, Cr, and Pb were identified. The PMF model identified four major pollution sources: aquaculture-related fish medicine (Factor 1, 17.9%), urban wastewater and farm feed (Factor 2, 30.5%), agricultural pesticide use (Factor 3, 17.3%), and maritime transportation (Factor 4, 34.3%). Discussion The results indicate that the primary contributors to trace metal pollution in the Wanning coastal area are human activities, including maritime transport, aquaculture, and agriculture. These findings highlight the need for targeted pollution control measures to ensure sustainable coastal development and marine environmental protection.

Quantitative analysis of anthocyanins and flavonoids in purple and green leaves of Eleutherococcus senticosus by UPLC-MS/MS techniques - Mei Hua; Meng Meng; Yu-pin Fu; Yun-qin Li (Natural Product Research, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Enhanced photosynthetic CO2 fixation in mutualistic Chlorella sp. and Mesorhizobium loti co-cultures - Dandan Yao; Yunhui Li; Kun Tian; Meng Wang; Ding Tan; Xingjia Fu; Yonghong Wu; Yun Liu; Hui Wang (Chemical Engineering Journal, 2025)

Chemical constituents of Euphorbia lathyris and their chemotaxonomic significance - Changchun Yuan; Yun Liang; Miao-Miao Xun; Yuqiang Li; Haixia Ji; Kai Fu (Biochemical Systematics and Ecology, 2025)

Noise suppression in elastic reverse time migration based on optimized pseudo-stress decoupling algorithm - Wenhao Lv; Qizhen Du; Fuyuan Zhang; Xiaoyu Zhang; Zhen Zou; Li-Yun Fu (Acta Geophysica, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Branch segmentation and phenotype extraction of apple trees based on improved Laplace algorithm - Long Li; Wei Fu; Bin Zhang; Yuqi Yang; Yun Ge; Congju Shen (Computers and Electronics in Agriculture, 2025)

Abrupt loss of species richness caused by ecosystem transition - Li Fu; Jianping Huang; Guolong Zhang; Dongliang Han; Lei Ding; Yun Wei; Xiaoyue Liu; Changyu Li; Haipeng Yu (Science Bulletin, 2025)

Thermoacoustoelasticity for Elastic Wave Propagation in Preheated and Prestressed Solid Rocks - Jian Yang; Li-Yun Fu; Tongcheng Han; Wubing Deng; Bo-Ye Fu (Rock Mechanics and Rock Engineering, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Deep-sea oil and gas plow-type cable broadband wide-azimuth 3D seismic acquisition and imaging - Yunfei Ye; Li-Yun Fu; Lijun Mi; Chuncai Chen; Zhenhua Jiao; Hanming Gu; Yu Wu (Science China Earth Sciences, 2025)

Gentidelasides A−G: Loganin derivatives from Gentiana delavayi with reducing Aβ secretion via suppressing BACE1 expression - Hai-Hui Guo; Chun-Xu Li; Min Yang; Feng-Feng Li; Hui-Yun Yang; Ming Yin; Jia-Peng Wang; Fu-Sheng Wang (Phytochemistry, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Anisotropic acoustoelastic effective-medium model for stress-dependent elastic moduli of fractured rocks - Bo-Ye Fu; Li-Yun Fu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Amyloid fibrils for β-carotene delivery – Influence of self-assembled structures on binding and in vitro release behavior - Congying Chen; Haifeng Wang; Qing Wang; Mengting Wang; David W. Everett; Min Huang; Yun Zhai; Teng Li; Yuying Fu (Food Chemistry, 2025)

Architectural coatings and temperature adaptive radiative cooling strategies applied in ten climate zones in China: Annual energy consumption reductions and potentials - Bin Li; Hong-Liang Zhang; Jun-Hao Chen; Ming-Ming Wu; Wei-Wei Wang; Fu-Yun Zhao; Yuguo Li (Energy and Buildings, 2025)

The Inversion of Seepage Parameters by Tidal and Barometric Response Methods: A Case Study of Shizhu Well with the Thick Aquifer Mixed with Mudstones - Qiuye Yang; Yan Zhang; Junliu Suwen; Xiao-long Sun; Tianming Huang; Junhua Hu; Shengwen Qi; Li-Yun Fu (Pure and Applied Geophysics, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Application of multi-angle spaceborne observations in characterizing the long-term particulate organic carbon pollution in China - Yun Hang; Qiang Pu; Qiao Zhu; Xia Meng; Zhihao Jin; Fengchao Liang; Hezhong Tian; Tiantian Li; Tijian Wang; Junji Cao; Qingyan Fu; Sagnik Dey; et al. (Science of The Total Environment, 2025)

A potential role for the interaction of Wolbachia surface proteins with the Drosophila microtubulin in maintenance of endosymbiosis and affecting spermiogenesis - Bin Mao; Ying-Ying Wang; Si-Ying Li; Yue Fu; Yun-Li Xiao; Yu-Feng Wang (Journal of Insect Physiology, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Mechanisms of radical regulation during carbamazepine degradation by UV-LED/chlorine process with different wavelengths in water - Qi Fu; Zhi Zhang; Yi-Li Lin; Tian-Yang Zhang; Yun-Lu Zhang; Renjie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Jian Lu; Zheng-Ning Luo; Chao Zeng; Huan He; et al. (Journal of Environmental Chemical Engineering, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Molecular phylogeny of Podoscypha (Basidiomycota, Podoscyphaceae) with descriptions of four new species, inferred from nuclear rDNA sequences - Fu-Chang Huang; Jian-Tian Lin; Hai-Fu Zheng; Yun-Long Liang; Miao-Miao Li; Cheng-Pei Ding (Mycological Progress, 2024)

Characterization of a short-term processing technology of black garlic with low 5-HMF content - Jun Liu; Jing Li; Shihao Ge; Xiaoyu Fu; Jiamin Zhu; Mengnan Wang; Yanrong Wang; Xiaoxiao Huang; Xinzheng Qin; Yixian Tu; Jun Xing; Chao Ma; et al. (Food Control, 2024)

Skeleton design engineering of covalent organic frameworks to enable in situ incorporation of coordination sites for improved extraction of uranyl ions - Jihe Zhao; Lei Zhao; Quan Cao; Guangying Fu; Fengwe Li; Huizhou Liu; Yun Fa (Chemical Engineering Journal, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Genomic characteristics of human respiratory syncytial virus from children in China during 2017-2020 - Fei Li; Yun Zhu; Qiuping Li; Xiaolei Guan; Hailin Zhang; Changchong Li; Meng Zhang; Lei Li; Yiliang Fu; Yali Duan; Luci Huang; Zhengde Xie; et al. (Archives of Virology, 2024)

Single and mixture toxicity of benzophenone-3 and its metabolites on Daphnia magna - Yun-Ru Ju; Chang-Rui Su; Chih-Feng Chen; Cheng-Fu Shih; Li-Siang Gu (Chemosphere, 2024)

Low-grade systemic inflammation links heavy metal exposures to mortality: A multi-metal inflammatory index approach - Yin Wang; Yuyan Wang; Ruizhen Li; Baiwen Ni; Ruixin Chen; Yun Huang; Rongrong Cheng; Pei Li; Han Li; Yang Peng; Xue Chen; Jingyu Wang; et al. (Science of The Total Environment, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

Rock-physics modeling and pre-stack seismic inversion for the Cambrian superdeep dolomite reservoirs in Tarim Basin, Northwest China - Shi-Kai Jian; Li-Yun Fu; Wensheng Duan; Gengxin Peng; Suo Cheng; Yongliang Tang; Duoming Zheng (Marine and Petroleum Geology, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Synergistic mechanism and toxicity reduction potential in medium-pressure UV/chlorine/TiO2 system for metronidazole removal - Yu-qiong Gao; Xiang-mei Zhong; Xue-ting Ren; Fu-xiang Tian; Nai-yun Gao; Cong Li (Journal of Water Process Engineering, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Polydopamine-assisted immobilization of metallic nanoparticles confined regionally in bamboo microchannels as continuous-flow microreactors for enhanced catalysis - Sisi Yao; Dengkang Guo; Shenjie Han; Zongying Fu; Shaoyi Lyu; Jingpeng Li; Yun Lu (Chemical Engineering Journal, 2024)

Chiral dual-core emitters based-on through-space coupling for high-performance OLEDs with little efficiency roll-off - Lifen Chen; Mingjia Deng; Shao-Yun Yin; Yu Fu; Yingxiao Mu; Jia-Xiong Chen; Lingyun Cui; Shaomin Ji; Yanping Huo; Hao-Li Zhang (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Diversity of endophytic bacterial community in rice roots and their roles in phosphate solubilization and plant growth - Weiqi Kuang; Weijun Chen; Chaobo Lei; Yujie Dai; Xiaodong Tian; Siyi Tang; Qiaoyan Qian; Chunyan Zhang; Lanxin Fu; Guoqing Zhou; Yun Wang; Huang Li (Rhizosphere, 2024)

The number of test organisms might influence the toxicity evaluation of hydrophobic micropollutants - Yun Yang; Xiangru Zhang; Longshan Fu; Can Li; Siwei Zhang (Chemosphere, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

Synergy of Mo doping and heterostructures in FeCo2S4@Mo-NiCo LDH/NF as durable and corrosion-resistance bifunctional electrocatalyst towards seawater electrolysis at industrial current density - Suyu Ge; Xueran Shen; Jiaxin Gao; Kaixuan Ma; Haoyu Zhao; Ruru Fu; Caihong Feng; Yun Zhao; Qingze Jiao; Hansheng Li (Chemical Engineering Journal, 2024)

Microwave co-pyrolysis of industrial sludge and waste biomass: Product valorization and synergistic mechanisms - Yang Liu; Asif Ali Siyal; Chunbao Zhou; Chenglong Liu; Jie Fu; Yingwen Zhang; Bang Yao; Li Chao; Huimin Yun; Jianjun Dai; Xiaotao Bi (Chemical Engineering Journal, 2024)

Establishment and characterization of cisplatin-resistant cell lines from canine mammary gland tumors - Mengxin Hu; Jie Li; Yunwei Fu; Enshuang Xu; Ding Li; Siqi Huang; Danning Tong; Shengzi Jin; Tongxu Guan; Yun Liu (Theriogenology, 2024)

Source term estimation for continuous plume dispersion in Fusion Field Trial-07: Bayesian inference probability adjoint inverse method - Hong-Liang Zhang; Bin Li; Jin Shang; Wei-Wei Wang; Fu-Yun Zhao (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Chuaria Walcott from the early Cambrian Qingjiang biota: a taxon persisted for billions of years - Rui-Yun Li; Dong-Jing Fu; Xing-Liang Zhang (Palaeoworld, 2024)

The effect of broad bean diet on structure, flavor and taste of fresh grass carp: A comprehensive study using E-nose, E-tongue, TPA, HS-SPME-GC-MS and LC-MS - Bing Fu; Mengping Zheng; Huici Yang; Junming Zhang; Yichao Li; Guangjun Wang; Jingjing Tian; Kai Zhang; Yun Xia; Zhifei Li; Wangbao Gong; Hongyan Li; et al. (Food Chemistry, 2024)

Thermal performance and ventilation analysis of a zigzag Trombe wall: Full numerical and experimental investigations - Hong-Liang Zhang; Bin Li; Dun-Ke Shi; Wei-Wei Wang; Fu-Yun Zhao (Energy and Buildings, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Coagulation/co-catalytic membrane integrated system for fouling-resistant and efficient water purification - Yun-Jie Wang; Chen-Xuan Li; Yan Meng; Zhi-Yan Guo; Shuo Cui; Xian-Zhong Fu; Hou-Qi Liu; Wen-Qi Xia; Wen-Wei Li (Water Research, 2024)

Development of trenchless rehabilitation for underground pipelines from an academic perspective - Dongmin Xi; Hongfang Lu; Xing Zou; Yun Fu; Houming Ni; Baicheng Li (Tunnelling and Underground Space Technology, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

Acoustoelastic DZ-MT model for stress-dependent elastic moduli of fractured rocks - Bo-Ye Fu; Li-Yun Fu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Experimental study on the regulation of NOX in co-pyrolysis of maize straw and woody biomass - Yongkun Fu; Yaohong Yu; Jinglun Qiang; Yun Deng; Sihao Ren; Hussien Elshareef; Huan Li; Renjie Dong; Yuguang Zhou (Fuel, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Multiple source tracking and identifications in urban regions with unstable wind flows: Particle swarm optimization methodologies and their benchmark solutions - Hong-Liang Zhang; Jun-Hao Chen; Bin Li; Wei-Wei Wang; Fu-Yun Zhao (Building and Environment, 2024)

Dynamic N transport and N2O emission during rainfall events in the coastal river - Wen-Xi Zhang; Fu-Jun Yue; Yong Wang; Yun Li; Yun-Chao Lang; Si-Liang Li (Science of The Total Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Reflection and Transmission of Inhomogeneous Plane Waves in Thermoporoelastic Media - Wanting Hou; Li-Yun Fu; José M. Carcione (Surveys in Geophysics, 2023)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Effects of heat stress on the chemical composition, oxidative stability, muscle metabolism, and meat quality of Nile tilapia (Oreochromis niloticus) - Yichao Li; Bing Fu; Junming Zhang; Guangjun Wang; Wangbao Gong; Jingjing Tian; Hongyan Li; Kai Zhang; Yun Xia; Zhifei Li; Jun Xie; Gen Kaneko; et al. (Food Chemistry, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Tree rings in Tsuga dumosa reveal increasing drought variability in subtropical southwest China over the past two centuries - Yun-Li Yin; Zaw Zaw; Xin-Hua Peng; Hui Zhang; Pei-Li Fu; Wen-Li Wang; Achim Bräuning; Ze-Xin Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Diode effects on street canyon ventilation in valley city: Temperature inversion and calm geostrophic wind - Jin Shang; Huai-Yu Zhong; Hong-Liang Zhang; Bin Li; Xiao-Xue Wang; Fu-Yun Zhao; Yuguo Li (Building and Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

Prediction of the Anisotropic Effective Moduli of Shales based on the Mori–Tanaka Model and the Digital Core Technique - Zidong Wang; Gongqi Cao; Jianlin Liu; Li-Yun Fu (Pure and Applied Geophysics, 2023)

Can the mix-charged NF membrane directly obtained by the interfacial polymerization of PIP and TMC? - Qiu-Yu Zhu; Zi-Yun Xu; Jie-Han Fu; Jie Huang; Zhen-Liang Xu; Min Tong; En-Chao Li; Yong-Jian Tang (Desalination, 2023)

Two new α-pyrone derivatives from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Qing-Hui Yan; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Ying Fu; You-Xing Zhao (Phytochemistry Letters, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Convergence and divergence emerging in climatic controls of polynomial trends for northern ecosystem productivity over 2000–2018 - Wenxin Zhang; Hongxiao Jin; Sadegh Jamali; Zheng Duan; Mousong Wu; Youhua Ran; Jonas Ardö; Lars Eklundh; Anna Maria Jönsson; Huaiwei Sun; Guojie Hu; Xiaodong Wu; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

PM-bound polycyclic aromatic compounds (PACs) in two large-scale petrochemical bases in South China: Spatial variations, sources, and risk assessment - Qiqi Li; Yuan Zeng; Yun Fan; Siqi Fu; Yufeng Guan; Yuxin Sun; Shejun Chen (Environmental Science and Pollution Research, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Combustion characteristics of three linear monohydric alcohols CH3(CH2)n-1OH (n = 16, 18, 22): Combined ignition experiments and molecular dynamics simulations - Xin Zhang; Yiming Zhao; Wenjuan Li; Yun Zhang; Siyu Xu; Sen Xu; Wen Zhou; Yizheng Fu; Yongan Feng; Weiguo Cao (Fuel, 2023)

Synergistic strategy design of (malonamide-amidoxime) bifunctional branching network crosslinked membrane and application in uranium (VI) resource recovery - Yang Li; Qi Ren; Rong Hua; Hong-Tao Xia; Xu-Xin Li; Ze-Yang Wang; Xuan Fu; Yan-Jun Du; Ze-Yi Yan; Yun Wang (Chemical Engineering Journal, 2023)

Thermal decomposition, flame propagation, and combustion reactions behaviours of stearic acid by experiments and molecular dynamic simulation - Wenjuan Li; Xin Zhang; Runqing Liu; Siyu Xu; Sen Xu; Yanhua Lan; Yizheng Fu; Yun Zhang; Yongan Feng; Weiguo Cao (Chemical Engineering Journal, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Heavy-metal resistant bio-hybrid with biogenic ferrous sulfide nanoparticles: pH-regulated self-assembly and wastewater treatment application - Xian-Zhong Fu; Jie Wu; Jie Li; Jian Ding; Shuo Cui; Xue-Meng Wang; Yun-Jie Wang; Hou-Qi Liu; Xin Deng; Dong-Feng Liu; Wen-Wei Li (Journal of Hazardous Materials, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Experimental and Numerical Investigations on Rock Breaking of TBM Disc Cutter Based on a Novel Platform with Rotational Cutting - Long-Chuan Deng; Fu-Bing Zhang; Xiao-Zhao Li; Chi Zhang; Yu-Kun Ji; Yun Wu (Rock Mechanics and Rock Engineering, 2023)

Factors influencing the transfer and abundance of antibiotic resistance genes in livestock environments in China - Z. F. Wang; H. Yun; S. Li; J. Ji; A. Khan; X. L. Fu; P. Zhang; X. K. Li (International Journal of Environmental Science and Technology, 2023)

An intelligent model for early kick detection based on cost-sensitive learning - Peng Chi; Li Qingfeng; Fu Jianhong; Yang Yun; Zhang Xiaomin; Su Yu; Xu Zhaoyang; Zhong Chengxu; Wu Pengcheng (Process Safety and Environmental Protection, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

Strong lateral heterogeneities of upper mantle shear-wave structures beneath the central and eastern Tien Shan - Qingya Tang; Weijia Sun; Songjian Ao; Li-Yun Fu; Wenjiao Xiao (International Journal of Earth Sciences, 2022)

Coupled Thermo–Mechanical Damage Evolution of Granite under Repeated Heating–Cooling Cycles and the Applications of Mohr–Coulomb and Drucker–Prager Models - Jian Yang; Li-Yun Fu; Fei Wang; Wubing Deng (Natural Resources Research, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Neuroprotection of Oral Edaravone on Middle Cerebral Artery Occlusion in Rats - Li-Qin Zhao; Ankit Parikh; Yun-Xia Xiong; Qing-Yan Ye; Ying-Guo; Xin-Fu Zhou; Hai-Yun Luo (Neurotoxicity Research, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Application of an improved hollow fiber liquid phase microextraction technique coupled to LC-MS/MS to studying migration of fluorescent whitening agents from plastic food contact materials - Wen-Li Zhou; Li Ding; Yun-Hui Cheng; Zhou Xu; Mao-Long Chen; Xian-Shu Fu (Food Additives & Contaminants: Part A, 2022)

Temperature- and Pressure-Dependent Pore Microstructures Using Static and Dynamic Moduli and Their Correlation - Jian Yang; Li-Yun Fu; Yonghao Zhang; Tongcheng Han (Rock Mechanics and Rock Engineering, 2022)

Effects of conservation measures on crop diversity and their implications for climate-resilient livelihoods: the case of Rupa Lake Watershed in Nepal - Yun-li Bai; Chao Fu; Balaram Thapa; Ram Balladur Rana; Lin-xiu Zhang (Journal of Mountain Science, 2022)
Agrobiodiversity conservation is vital for achieving sustainability, but empirical studies on the effects of different practices or measures on crop diversity are rare. This study aims to estimate the effects of raising conservation awareness (RCA), building diversity blocks (BDB), and their combination on crop diversity among 240 randomly selected households surrounding the Rupa Lake Watershed in Nepal. Based on descriptive analysis and multiple regression models, the results indicate that the two single measures had no significant effect on the numbers of crop species and varieties grown by households in 2018. However, the combination of RCA and BDB had a significantly positive effect on the number of crop varieties, especially for grain and vegetable crops. Considering that these crops are essential in the daily lives of local people, the results indicate that a strategy that combines both awareness raising and on-farm conservation measures can generate higher crop diversity and better serve the climate-resilient livelihoods of people in mountainous areas.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Chemical composition and anti-hepatoma effect of Annona squamosa L. pericarp oil - Ya-Yun Chen; Fu-Qiang Li; Xiao-Li Zhu; Jian-Wei Chen; Xiang Li (Natural Product Research, 2022)

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

Genome-Wide Characterization of Aquaporins (aqps) in Lateolabrax maculatus: Evolution and Expression Patterns During Freshwater Acclimation - Xiaoyan Zhang; Peng Yu; Haishen Wen; Xin Qi; Yuan Tian; Kaiqiang Zhang; Qiang Fu; Yun Li; Chao Li (Marine Biotechnology, 2021)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Resource status and protection strategies of mangroves in China - Xiu-Mei Fu; Hui-Ying Tang; Yang Liu; Meng-Qi Zhang; Shan-Shan Jiang; Fang Yang; Xiao-Yan Li; Chang-Yun Wang (Journal of Coastal Conservation, 2021)
Mangrove is a typical natural landscape with great ecological, social and economic functions and values, and should be highly valued and protected. However, in the past few decades, mangrove resources have suffered serious damage, and there are also many deficiencies in mangrove protection. Chinese mangroves, as an important part of the global mangroves, are of great research value. In the present study, the status and historical dynamic process of Chinese mangrove resources were investigated and discussed to illustrate the problems of resources from three aspects, including mangrove distribution, area and plant species. Based on field research, literature research and data analysis, it was revealed that Chinese mangroves are distributed in eight provinces and regions along the southeast coast with an area of 35,749.25 hm 2 , 38 species and 40 nature reserves. The protection situation and deficiencies were analyzed from the establishment and management of nature reserves. Based on the resource status and problems, reasonable strategies were proposed to protect and manage mangroves mainly from four aspects, including publicity and education, resources restoration and protection technology, legal system establishment, and comprehensive protection and management.

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Soil fertility, enzyme activity, and microbial community structure diversity among different soil textures under different land use types in coastal saline soil - Yun Zhu; Bin Guo; Chen Liu; Yicheng Lin; Qinglin Fu; Ningyu Li; Hua Li (Journal of Soils and Sediments, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Gut microbiome alterations and its link to corticosteroid resistance in immune thrombocytopenia - Yanan Wang; Fengqi Liu; Gaochao Zhang; Yan Su; Xueyan Sun; Qi Chen; Chencong Wang; Haixia Fu; Yun He; Xiaolu Zhu; Xiao Liu; Meng Lv; et al. (Science China Life Sciences, 2021)

Distribution of gas hydrate in fractured reservoirs: Insights from anisotropic seismic measurements - Shengbiao Liu; Tongcheng Han; Li-Yun Fu (Science China Earth Sciences, 2021)

Integrated LSM-DFN Modeling of Naturally Fractured Reservoirs: Roughness Effect on Elastic Characteristics - Ning Liu; Yang-Ying Li; Li-Yun Fu; Yue Kong; Wu-Shuang Li (Pure and Applied Geophysics, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Elastic wave propagation and scattering in prestressed porous rocks - Li-Yun Fu; Bo-Ye Fu; Weijia Sun; Tongcheng Han; Jianlin Liu (Science China Earth Sciences, 2020)

Combined effects of green manure returning and addition of sewage sludge compost on plant growth and microorganism communities in gold tailings - Yan-Jun Ai; Fu-Ping Li; Hai-Hong Gu; Xiao-Jie Chi; Xue-Tao Yuan; Dong-Yun Han (Environmental Science and Pollution Research, 2020)

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Identification of a novel mutant spp1 that specifies the identity of inflorescence meristem in rice - Peizhou Xu; Asif Ali; Yun Li; Hongyu Zhang; Xiaoqiong Chen; Shaohong Fu; Yang Jin; Zhongwei Zhang; Shu Yuan; Xianjun Wu (Plant Biosystems, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

The synergetic effect of pelvic rotation and X-ray offset on radiographic angles of the acetabular cup - Jing-Xin Zhao; Xiu-Yun Su; Zhe Zhao; Ruo-Xiu Xiao; Guo-Fei Sun; Li-Cheng Zhang; Pei-Fu Tang (Medical & Biological Engineering & Computing, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Synthesis and biological evaluation of novel disulfides incorporating 1,3,4-thiadiazole scaffold as promising antitumor agents - Sha Li; Hai-Xin Wang; Hai-Ying Liu; Fen Jing; Xiao-Yun Fu; Cai-Wen Li; Yan-Ping Shi; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Effect of male sterile and fertile cytoplasm on nuclear DNA methylation in hybrid rice - Asif Ali; Yun Li; Hui Chen; Peizhou Xu; Hongyu Zhang; Xiaoqiong Chen; Liao Yongxiang; Shaohong Fu; Tingkai Wu; Muhammad Zafar Iqbal; Muhammad Umer Farooq; Xianjun Wu (Acta Physiologiae Plantarum, 2019)

Regulation of flowering time via miR172-mediated APETALA2-like expression in ornamental gloxinia (Sinningia speciosa) - Xiao-yan Li; Fu Guo; Sheng-yun Ma; Mu-yuan Zhu; Wei-huai Pan; Hong-wu Bian (Journal of Zhejiang University-SCIENCE B, 2019)

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Gram-negative bacilli-derived peptide antibiotics developed since 2000 - Yun Xue; Mengya Wang; Pengchao Zhao; Chunshan Quan; Xin Li; Lina Wang; Weina Gao; Jinghua Li; Xiangyang Zu; Dongliao Fu; Shuxiao Feng; Ping Li (Biotechnology Letters, 2018)

Two thymol derivatives from the flower buds of Lonicera japonica and their antibacterial activity - Jing Yang; Yong-Chao Li; Xiu-Ren Zhou; Xin-Juan Xu; Qing-Yun Fu; Chang-Zhong Liu (Natural Product Research, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Stress-Associated Intrinsic and Scattering Attenuation from Laboratory Ultrasonic Measurements on Shales - Junhua Hu; Li-Yun Fu; Wei Wei; Yan Zhang (Pure and Applied Geophysics, 2018)

Maternal doubled haploid production in interploidy hybridization between Brassica napus and Brassica allooctaploids - Shaohong Fu; Liqin Yin; Mingchao Xu; Yun Li; Maolin Wang; Jin Yang; Tingdong Fu; Jisheng Wang; Jinxiong Shen; Asif Ali; Qiong Zou; Bin Yi; et al. (Planta, 2018)

Physical interactions and mutational analysis of MoYpt7 in Magnaporthe oryzae - Lu-yao Huang; Min Wu; Xiao-yun Yu; Lin Li; Fu-cheng Lin; Xiao-hong Liu (Journal of Zhejiang University-SCIENCE B, 2018)

Genome sequencing and phylogenetic analysis of Banna virus (genus Seadornavirus, family Reoviridae) isolated from Culicoides - Song Song; Yuanyuan Li; Shihong Fu; Wenwen Lei; Xiaofang Guo; Yun Feng; Xiaoyan Gao; Xiaolong Li; Zhonghua Yang; Ziqian Xu; Ying He; Huanyu Wang; et al. (Science China Life Sciences, 2017)

The nitrate‐reduction gene cluster components exert lineage‐dependent contributions to optimization of Sinorhizobium symbiosis with soybeans - Li Xue Liu; Qin Qin Li; Yun Zeng Zhang; Yue Hu; Jian Jiao; Hui Juan Guo; Xing Xing Zhang; Biliang Zhang; Wen Xin Chen; Chang Fu Tian (Environmental Microbiology, 2017)
Summary Receiving nodulation and nitrogen fixation genes does not guarantee rhizobia an effective symbiosis with legumes. Here, variations in gene content were determined for three Sinorhizobium species showing contrasting symbiotic efficiency on soybeans. A nitrate‐reduction gene cluster absent in S. sojae was found to be essential for symbiotic adaptations of S. fredii and S . sp. III. In S. fredii , the deletion mutation of the nap (nitrate reductase), instead of nir (nitrite reductase) and nor (nitric oxide reductase), led to defects in nitrogen‐fixation (Fix – ). By contrast, none of these core nitrate‐reduction genes were required for the symbiosis of S . sp. III. However, within the same gene cluster, the deletion of hemN1 (encoding oxygen‐independent coproporphyrinogen III oxidase) in both S. fredii and S . sp. III led to the formation of nitrogen‐fixing (Fix + ) but ineffective (Eff – ) nodules. These Fix + /Eff – nodules were characterized by significantly lower enzyme activity of glutamine synthetase indicating rhizobial modulation of nitrogen‐assimilation by plants. A distant homologue of HemN1 from S. sojae can complement this defect in S. fredii and S . sp. III, but exhibited a more pleotropic role in symbiosis establishment. These findings highlighted the lineage‐dependent optimization of symbiotic functions in different rhizobial species associated with the same host.

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Haplotype of platelet receptor P2RY12 gene is associated with residual clopidogrel on-treatment platelet reactivity - Xiao-yan Nie; Jun-lei Li; Yong Zhang; Yang Xu; Xue-li Yang; Yu Fu; Guang-kai Liang; Yun Lu; Jian Liu; Lu-wen Shi (Journal of Zhejiang University-SCIENCE B, 2017)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Boundary-reflected waves and ultrasonic coda waves in rock physics experiments - Bo-Ye Fu; Li-Yun Fu; Wei Wei; Yan Zhang (Applied Geophysics, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Computation of elastic properties of 3D digital cores from the Longmaxi shale - Wen-Hui Zhang; Li-Yun Fu; Yan Zhang; Wei-Jun Jin (Applied Geophysics, 2016)

Plasma Homocysteine Levels Predict the Risk of Acute Cerebral Infarction in Patients with Carotid Artery Lesions - Wei Wu; Yi Guan; Kan Xu; Xi-Jia Fu; Xiao-Feng Lei; Li-Jian Lei; Zhi-Qing Zhang; Yan Cheng; Yun-Qian Li (Molecular Neurobiology, 2016)

One new 19- nor cucurbitane-type triterpenoid from the stems of Momordica charantia - Yong-chao Li; Xin-juan Xu; Jing Yang; Xing-gang Wu; Qing-yun Fu (Natural Product Research, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

Imbalanced expression of Bcl-xL and Bax in platelets treated with plasma from immune thrombocytopenia - Jianlin Qiao; Yun Liu; Depeng Li; Yulu Wu; Xiaoqian Li; Yao Yao; Mingshan Niu; Chunling Fu; Hongchun Li; Ping Ma; Zhenyu Li; Kailin Xu; et al. (Immunologic Research, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

High abundances of dicarboxylic acids, oxocarboxylic acids, and α-dicarbonyls in fine aerosols (PM2.5) in Chengdu, China during wintertime haze pollution - Xiao-dong Li; Zhou Yang; Pingqing Fu; Jing Yu; Yun-chao Lang; Di Liu; Kaori Ono; Kimitaka Kawamura (Environmental Science and Pollution Research, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Genetic diversity and differentiation in the critically endangered orchid (Amitostigma hemipilioides): implications for conservation - Qin Yang; Yan Fu; Yong-qing Wang; Yun Wang; Wen-hua Zhang; Xing-yuan Li; Yong-Quan Reng; Jie Zhang (Plant Systematics and Evolution, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

New 18-oxygenated polyhydroxy steroid from a South China Sea soft coral Sarcophyton sp. - Ling-Ling Sun; Xiu-Mei Fu; Xiu-Bao Li; Qian Xing; Chang-Yun Wang (Natural Product Research, 2013)

Approximate Solutions to the Boundary–Volume Integral Equation for Wave Propagation in Piecewise Heterogeneous Media - Geng-Xin Yu; Li-Yun Fu (Pure and Applied Geophysics, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

Synthesis, characterization, and antitumor activity of rare earth metal complexes of benzoic acid nitrogen mustard - Sufeng Zhou; Yun Fu; Xizhi Fan; Yanfang Zhang; Changzheng Li (Medicinal Chemistry Research, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Characterization of carbonic anhydrase II from Chlorella vulgaris in bio-CO2 capture - Li Li; Ming-lai Fu; Yong-hao Zhao; Yun-tian Zhu (Environmental Science and Pollution Research, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Cloning and characterization of a maize bZIP transcription factor, ZmbZIP72, confers drought and salt tolerance in transgenic Arabidopsis - Sheng Ying; Deng-Feng Zhang; Jing Fu; Yun-Su Shi; Yan-Chun Song; Tian-Yu Wang; Yu Li (Planta, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Isolation and alga-inhibiting characterization of Vibrio sp. BS02 against Alexandrium tamarense - Lijun Fu; Xinli An; Dong Li; Lijian Zhou; Yun Tian; Tianling Zheng (World Journal of Microbiology and Biotechnology, 2011)

Up-regulation of mitochondrial antioxidation signals in ovarian cancer cells with aggressive biologic behavior - Yue Wang; Li Dong; Heng Cui; Dan-hua Shen; Ying Wang; Xiao-hong Chang; Tian-yun Fu; Xue Ye; Yuan-yang Yao (Journal of Zhejiang University-SCIENCE B, 2011)

Slit2/Robo1 signaling in glioma migration and invasion - Yun Xu; Li Wen-Liang; Fu Li; Gu Feng; Ma Yong-Jie (Neuroscience Bulletin, 2010)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Targeted antitumor effect induced by hTERT promoter mediated ODC antisense adenovirus - Wei Wang; Bin Jin; Wei Li; Chun-Xiao Xu; Fu-Ai Cui; Bin Liu; Yun-Fei Yan; Xian-Xi Liu; Xiu-Li Wang (Molecular Biology Reports, 2010)

2-(3,5-Dibromo-4-hydroxyphenyl)imidazo[4,5-f][1,10]phenanthrolinoruthenium(II) complexes: synthesis, characterization, cytotoxicity, apoptosis, DNA-binding and antioxidant activity - Yun-Jun Liu; Zhen-Hua Liang; Zheng-Zheng Li; Cheng-Hui Zeng; Jun-Hua Yao; Hong-Liang Huang; Fu-Hai Wu (BioMetals, 2010)

Dynamic changes of territories 17 and 18 during EBV-infection of human lymphocytes - Chunxiang Li; Zhongcheng Shi; Liqiu Zhang; Yun Huang; An Liu; Yan Jin; Yang Yu; Jing Bai; Dieyan Chen; Christi Gendron; Xinghan Liu; Songbin Fu (Molecular Biology Reports, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Infection and replication of avian influenza H5N1 virus in an infected human - Jing-Jiao Zhou; Dan-Yun Fang; Jie Fu; Jiang Tian; Jun-Mei Zhou; Hui-Jun Yan; Yu Liang; Li-Fang Jiang (Virus Genes, 2009)

Improvement of arachidonic acid and eicosapentaenoic acid production by increasing the copy number of the genes encoding fatty acid desaturase and elongase into Pichia pastoris - Yun-Tao Li; Mao-Teng Li; Chu-Hua Fu; Peng-Peng Zhou; Jian-Min Liu; Long-Jiang Yu (Biotechnology Letters, 2009)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Molecular cloning and characterization of a novel transcript variant of Mtsarg1 gene - Li Li; Gang Liu; Jun-Jiang Fu; Lu-Yun Li; Xiao-Jun Tan; Sheng Yang; Guang-Xiu Lu (Molecular Biology Reports, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Improving ovary and embryo culture techniques for efficient resynthesis of Brassica napus from reciprocal crosses between yellow-seeded diploids B. rapa and B. oleracea - Jing wen; Jin-xing Tu; Zai-yun Li; Ting-dong Fu; Chao-zhi Ma; Jin-xiong Shen (Euphytica, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Chemical composition, antimicrobial and antioxidant activities of the essential oil of Tibetan herbal medicine Dracocephalum heterophyllum Benth - ChunJiang Zhang; HongYu Li; Tian Yun; YongHong Fu; ChunMei Liu; Bu Gong; BenJia Neng (Natural Product Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Agrobacterium-mediated transformation of cotton (Gossypium hirsutum L. cv. Zhongmian 35) using glyphosate as a selectable marker - Fu-Yong Zhao; Yun-Feng Li; Peilin Xu (Biotechnology Letters, 2006)

Identification and expression analysis of alternatively spliced isoforms of human interleukin-23 receptor gene in normal lymphoid cells and selected tumor cells - Xiang-Yue Zhang; Hai-Jing Zhang; Yun Zhang; Ying-Jie Fu; Jie He; Li-Ping Zhu; Shu-Hui Wang; Li Liu (Immunogenetics, 2006)

Genome-wide Introgression Lines and their Use in Genetic and Molecular Dissection of Complex Phenotypes in Rice (Oryza sativa L.) - Zhi-Kang Li; Bin-Ying Fu; Yong-Ming Gao; Jian-Long Xu; J. Ali; H. R. Lafitte; Yun-Zhu Jiang; J. Domingo Rey; C. H. M. Vijayakumar; R. Maghirang; Tian-Qing Zheng; Ling-Hua Zhu (Plant Molecular Biology, 2005)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Protective effects of adenoviral cardiotrophin-1 gene transfer on rubrospinal neurons after spinal cord injury in adult rats - Zheng-Feng Zhang; Wei-Hong Liao; Qing-Feng Yang; Hong-Yun Li; Ya-Min Wu; Xin-Fu Zhou (Neurotoxicity Research, 2003)